How Parental Substance Abuse Affects Family Functioning and Child Psychological Health - Rahimi , Leili; Ahmadi Shooli , Zahra (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aims to explore the impact of parental substance abuse on family functioning and the psychological health of children. Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews to gather data from 21 participants who are children of substance-abusing parents in Tehran. The participants were selected using purposive sampling to ensure a diverse representation of different family dynamics and experiences. Thematic analysis was applied to the interview transcripts to identify recurring patterns and themes related to family functioning, emotional distress, and behavioral issues. Findings: The study revealed several key findings: (1) children of substance-abusing parents often experience family dysfunction, including inconsistent caregiving, poor communication, and emotional neglect; (2) the intergenerational transmission of substance abuse and maladaptive behaviors was commonly reported; (3) children frequently assumed caregiver roles (parentification) due to their parents’ inability to fulfill their caregiving responsibilities; (4) social isolation and stigma were significant factors contributing to the children’s emotional and psychological distress; and (5) children of substance-abusing parents exhibited elevated levels of anxiety, depression, and maladaptive coping strategies. These findings align with existing literature, reinforcing the negative effects of parental substance abuse on children’s well-being. Conclusion: The study underscores the profound psychological and emotional impact that parental substance abuse has on children, highlighting the need for targeted interventions that address both familial and individual needs. Children exposed to substance abuse require emotional support and therapeutic services to mitigate the long-term consequences of growing up in such environments.